Revisão taxonômica das espécies sul-americanas de Heilus Kuschel, 1955 (Curculionidae, Molytinae, Hylobiini) - Lira, Aline de Oliveira (2018)
The Genus Heilus Kuschel, 1955 (Coleoptera, Curculionidae) was defined by the presence of a basal fold in the first abdominal ventrite that was strongly dilated behind the metacoxas. The 18 species of the genus are exclusive to the Neotropical Region, and the present study refers to the taxonomic revision of the 14 species distributed in South America. Based on the morphological analysis of adult males and females it was possible to add new characters for the recognition of Heilus, mainly related to the lining of the integument and genitalia, with also allowed the identification of nine new species. The male and female genitalia of the valid species and all new species, as well as the mouthparts of the type specie H. inaequalis were illustrated. The sclerites observed in the inner sac and the middle lobe were fundamental for interspecific differentiation, and homology analysis could support future studies in the Heilus phylogeny. A new synonym was proposed between H. tuberculosus and H. ochrifer, and the first occurrence record of H. iniquus presented to Brazil. The geographic distribution of the valid species was expanded, especially for Brazil, and a taxonomic key for the identification of the South American species of Heilus, made.